48th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2012
DOI: 10.2514/6.2012-4122
|View full text |Cite
|
Sign up to set email alerts
|

Flowfield and Heat Transfer Characteristics of Cooling Channel Flows in a Methane-Cooled Thrust Chamber

Abstract: In recent years, methane has attracted attention as a propellant for liquid rocket engines because of its various advantages compared to typical propellants such as hydrogen. When methane is used as a coolant for a regenerative cooling system, its near-critical thermodynamic and transport properties experience large variations because its critical pressure is higher than that of typical propellants; this significantly influences the flowfield and heat transfer characteristics. Therefore, adequate understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…2 that occur in the combustion chambers. [16][17][18][19][20][21][22][23][24] As a result, it was confirmed that CRUNCH CFD is an effective CFD tool to predict key physical phenomena in regeneratively cooled combustion chambers qualitatively and quantitatively. Furthermore, a conjugated combustion and heat transfer simulation methodology was recently proposed as a practical strategy that can model a full-scale combustion chamber and predict regenerative cooling performance.…”
Section: Introductionsupporting
confidence: 59%
“…2 that occur in the combustion chambers. [16][17][18][19][20][21][22][23][24] As a result, it was confirmed that CRUNCH CFD is an effective CFD tool to predict key physical phenomena in regeneratively cooled combustion chambers qualitatively and quantitatively. Furthermore, a conjugated combustion and heat transfer simulation methodology was recently proposed as a practical strategy that can model a full-scale combustion chamber and predict regenerative cooling performance.…”
Section: Introductionsupporting
confidence: 59%
“…Most investigations implemented coupled heat transfer to simulate asymmetrically heated cooling channels because the temperature fields of the fluid region obtained with and without wall heat conduction are significantly different [2]. Previous studies showed that the selected geometries, fluids (hydrogen, nitrogen, methane), and boundary conditions were close to those expected in the regenerative cooling system of rocket engines (Froelich et al [3], Neuner et al [4], Jung et al [5], DiValentin and Naraghi [6], Kang and Sun [7], Pizzarelli et al [2,[8][9][10][11][12][13][14], Negishi et al [15], Ruan and Meng [16], and Wang et al [17]). A high aspect ratio cooling channel (HARCC) has been widely used in the regenerative cooling system of rocket engines.…”
Section: Introductionmentioning
confidence: 82%
“…As the fluid enters the curved section, the secondary flow streamlines obtained by the SA model and RSM become similar, that is, the flow is pushed against the concave wall near the channel midplane and pulled from the concave wall near the side wall (see15 and 45 deg cross sections of Fig. 7).…”
mentioning
confidence: 91%
“…Before moving to the next downstream node, the coolant temperature increment by absorbing the heat flux and pressure losses due to friction and local flow resistances through the current channel segment are computed by Eqs. (15) and (17), respectively. Whenever the coolant temperature and pressure are updated, the thermophysical properties of the coolant are interpolated from the preconstructed lookup table, as mentioned in Subsection 2.4.…”
Section: Effective Modeling Of Conjugate Heat Transfer 873mentioning
confidence: 98%
“…Kang and Sun [14] simulated the convective and radiative heat transfer of the hot gas, heat conduction within the channel, and the coolant flow in a regeneratively cooled rocket nozzle in a fully coupled manner to assess the modeling effects such as chemistry, radiation, and empirical correlations. Negishi et al [15] calculated conjugate heat transfer between coolant flow and heat conduction for a subscale methane-cooled thrust chamber with focus on the large property variation occurring in the transcritical flow. In their simulation, the computational grid system of about fifty millions is used for a circumferential half of the thrust chamber, including coolant manifolds, cooling channels, and chamber liners, while distribution of the wall heat flux on EFFECTIVE MODELING OF CONJUGATE HEAT TRANSFER 865 the hot-gas side is prescribed as thermal boundary condition from another hot-firing test with a calorimetric chamber.…”
Section: Introductionmentioning
confidence: 99%